The influence of live streaming shopping tiktok and product quality on purchase decisions with e-trust as mediataion (study on skintific moisturizer products) - Deva, salsabilla; Azazi, Anwar; Pebrianti, Wenny; I. K, Maria Christiana; Fahruna, Yulyanti (Junal Ilmu Manajemen, 2024)
This research was conducted to find out whether sales via Live Streaming TikTok Shop, as well as the product quality of Skintific moisturizer products, are able to increase consumer e-trust in purchasing decisions for Skintific moisturizer products. This research is quantitative research, with data obtained from 215 respondents in Indonesia who were selected using purposive sampling techniques. The sample respondents in this study were people aged at least 17 years who used the TikTok application, had watched TikTok Live Shopping conducted by Skintific, and had purchased Skintific moisturizer products in the last six months. The data processing tool that will be used is the AMOS version 24 application with data analysis using Structural Equation Modeling. From the research that has been carried out, it was found that Live Streaming Shopping and Product quality have a positive and significant effect on e-Trust. The indirect relationship between Live Streaming Shopping on TikTok and e-trust is effective in increasing purchasing decisions. Likewise, the indirect relationship between product quality and e-trust is also effective in improving purchasing decisions. These findings contribute to the literature by showing that Live Streaming Shopping and Product quality have a positive influence on Indonesian people's purchasing decisions regarding Skintific moisturizer products. Apart from that, there is a significant influence of e-trust on purchasing decisions, which illustrates how consumer trust in Skintific moisturizer products is able to encourage consumers to buy these moisturizer products.